Peran Alat Bukti Petunjuk Bagi Hakim dalam Memutus Perkara Pidana di Indonesia - Sengi, Ernest; Usak, Usak (Wajah Hukum, 2025)
Proof is the central point in resolving criminal cases. Whether a defendant is convicted or not depends on the evidence. Proving, means trying to convince the judge about whether the defendant is guilty or not. Of course, it is based on the evidentiary parameters stipulated in the law. One of the evidentiary parameters is the evidentiary strength (bewijskracht) of each piece of evidence. Guidance evidence are one of the means of evidence as regulated in Article 184 of the Criminal Procedure Code. The legal issue that is the aim of the research is to analyze the role of guiding evidence for judges in deciding criminal cases; because in legal practice the evidence of guidance is very dependent on the judge's subjective assessment in deciding the case. Because what is being studied is the role of guidance evidence, the approach used is a statutory approach. The results of the research show that guidance evidence is complementary evidence or accessory evidence which is only found through other evidence, namely witness statements, letters and defendant statements. Guidance evidence is one of the legal pieces of evidence in Indonesian Criminal Procedure Law which has the role and function of strengthening the evidentiary process in resolving criminal cases. Even though guidance evidence is not direct evidence, guidance evidence has the same position as other evidence in the Criminal Procedure Code.